1998
DOI: 10.1111/j.1749-6632.1998.tb08325.x
|View full text |Cite
|
Sign up to set email alerts
|

Brown Adipose Tissue: More Than an Effector of Thermogenesis?a

Abstract: Brown adipose tissue (BAT) produces heat by oxidation of fatty acids. This takes place when the tissue is stimulated by norepinephrine; the molecular background for the ability of BAT to produce heat is the tissue-specific mitochondrial protein UCP1. In the classic view of BAT with respect to fever, BAT is an effector organ, producing heat especially during the onset phase of the fever. There is good evidence that BAT thermogenesis is stimulated via a lipopolysaccharide (LPS), interleukin (IL)-1 beta, IL-6, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(79 citation statements)
references
References 55 publications
3
73
0
3
Order By: Relevance
“…In addition, the CR animals may find the development of a fever too metabolically costly due to their already reduced metabolic rate (22). A limitation of the present study was the lack of measuring brown fat thermogenesis, which has been shown to be reduced in CR rats (62); there have been suggestions of a correlation between the amount of brown fat and fever intensity, with reduced levels of brown fat being linked to reduced fever intensity (10). However, it is important to note that the thermogenic ability of the CR25% and CR50% mice was intact, as evidenced by the locomotor activity, induced increase in T b prior to being fed during the CR period (data not shown).…”
Section: Cr and Sickness Behaviormentioning
confidence: 87%
“…In addition, the CR animals may find the development of a fever too metabolically costly due to their already reduced metabolic rate (22). A limitation of the present study was the lack of measuring brown fat thermogenesis, which has been shown to be reduced in CR rats (62); there have been suggestions of a correlation between the amount of brown fat and fever intensity, with reduced levels of brown fat being linked to reduced fever intensity (10). However, it is important to note that the thermogenic ability of the CR25% and CR50% mice was intact, as evidenced by the locomotor activity, induced increase in T b prior to being fed during the CR period (data not shown).…”
Section: Cr and Sickness Behaviormentioning
confidence: 87%
“…Based on the evidence that epinephrine treatment of cultured brown adipocytes in culture media increases IL-6 (23,24), and the well-established effects of IL-6 in promoting lipolysis in WAT (34,35), we propose a model whereby BAT-derived IL-6 promotes lipolysis, resulting in the observed reduction in adipocyte size. Another potential mechanism through which IL-6 could promote increased insulin sensitivity and glucose metabolism is an increase in GLUT1 expression, which is observed in the WAT and hearts of mice receiving BAT.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there was no change in basal temperature in mice receiving transplants of BAT compared with sham-operated mice (Supplemental Figure 4, A and B). Instead of an inflammatory response -given that FGF21 concentrations are increased by BAT transplantation, that norepinephrine treatment of BAT in culture can result in secretion of IL-6 (23,24), and that mice overexpressing IL-6 have an improved metabolic profile (25) -we hypothesize that IL-6 and FGF21 work together to regulate glucose metabolism.…”
Section: Transplantation Of Bat Improves Glucose Tolerance and Insulimentioning
confidence: 99%
“…The transcriptional co-activator peroxisome proliferator-activated receptor-γ coactivator 1α (PGC-1α) is a key regulator of signaling pathways that promote mitochondrial biogenesis and bioenergetics in cardiomyocytes, and PGC-1α regulates peroxisome proliferator-activated receptor α (PPARα) to enhance the transcription of mitochondrial fatty acid β-oxidation enzymes (Wu et al, 1999;Lehman et al, 2000;Vega et al, 2000). It interacts with a broad range of transcription factors, including nuclear hormone receptors, nuclear respiratory factors, and specific transcription factors, to regulate glucose metabolism and response to environmental stimuli such as cold exposure and prolonged starvation (Cannon et al, 1998;Meirhaeghe et al, 2003;Lin et al, 2005). Consistent with these roles, it is expressed at high levels in tissues with a high energy demand, such as brain, kidney, cardiac, and skeletal muscle (Lin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%